The Role of Work Motivation, Professional Competence, and School Climate in Improving Teacher Performance at SMAN 1 Karang Baru Aceh Tamiang - Lubis, Syaiful Bahri; Hutagalung, Eko Prawira; Azwar, Ahmad; Pasaribu, Candra; Pasaribu, Dian Hardiansyah; Naerus, Mila (Jurnal EMT KITA, 2025)
This research examines the impact of work motivation, professional competence, and school climate on teacher performance at SMAN 1 Karang Baru, Aceh Tamiang. Teacher performance plays a pivotal role in determining the quality of education, making it imperative to understand the factors that contribute to its enhancement. This study employs a quantitative approach, utilizing survey methods and multiple regression analysis to investigate these relationships. Data were gathered through a structured questionnaire distributed to 50 teachers, with responses analyzed for validity and reliability. The findings reveal that work motivation, professional competence, and school climate significantly influence teacher performance, with work motivation and professional competence exerting a more substantial effect compared to school climate. These results highlight the critical importance of fostering motivation through appropriate incentives, recognition, and career development opportunities. Similarly, the enhancement of professional competence through continuous training and pedagogical skill development is paramount. Although the school climate also plays a role, its impact is relatively moderate, suggesting that personal factors such as motivation and competence are more influential. The study underscores the necessity of targeted interventions to improve teacher performance, emphasizing strategies that enhance motivation and professional competence while cultivating a positive and supportive school environment. These findings are expected to inform policies aimed at advancing educational quality in schools.